Kunitz-Type Peptide HCRG21 from the Sea Anemone Heteractis crispa Is a Full Antagonist of the TRPV1 Receptor - Margarita Monastyrnaya; Steve Peigneur; Elena Zelepuga; Oksana Sintsova; Irina Gladkikh; Elena Leychenko; Marina Isaeva; Jan Tytgat; Emma Kozlovskaya (Marine Drugs, 2016)
Sea anemone venoms comprise multifarious peptides modulating biological targets such as ion channels or receptors. The sequence of a new Kunitz-type peptide, HCRG21, belonging to the Heteractis crispa RG (HCRG) peptide subfamily was deduced on the basis of the gene sequence obtained from the Heteractis crispa cDNA. HCRG21 shares high structural homology with Kunitz-type peptides APHC1–APHC3 from H. crispa, and clusters with the peptides from so named “analgesic cluster” of the HCGS peptide subfamily but forms a separate branch on the NJ-phylogenetic tree. Three unique point substitutions at the N-terminus of the molecule, Arg1, Gly2, and Ser5, distinguish HCRG21 from other peptides of this cluster. The trypsin inhibitory activity of recombinant HCRG21 (rHCRG21) was comparable with the activity of peptides from the same cluster. Inhibition constants for trypsin and α-chymotrypsin were 1.0 × 10−7 and 7.0 × 10−7 M, respectively. Electrophysiological experiments revealed that rHCRG21 inhibits 95% of the capsaicin-induced current through transient receptor potential family member vanilloid 1 (TRPV1) and has a half-maximal inhibitory concentration of 6.9 ± 0.4 μM. Moreover, rHCRG21 is the first full peptide TRPV1 inhibitor, although displaying lower affinity for its receptor in comparison with other known ligands. Macromolecular docking and full atom Molecular Dynamics (MD) simulations of the rHCRG21–TRPV1 complex allow hypothesizing the existence of two feasible, intra- and extracellular, molecular mechanisms of blocking. These data provide valuable insights in the structural and functional relationships and pharmacological potential of bifunctional Kunitz-type peptides.